Zaitzevia tangliangi sp. nov. a new riffle beetle from China (Coleoptera:Elmidae: Macronychini) - Jiang, Ri-Xin; Wang, Shuo (Zootaxa, 2021)
A new riffle beetle of the genus Zaitzevia Champion, 1923, Z. tangliangi sp. nov. from Hubei Province, China is described. Habitus and other diagnostic features of the new species are described and illustrated. Habitat information and collection data of the new species are also provided.